From serfdom to hipsterhood: Folk music across villages and cities. A conversation between Andrzej Bieńkowski and Piotr Grochowski - Bieńkowski, Andrzej; Grochowski, Piotr (Literatura Ludowa. Journal of Folklore and Popular Culture, 2021)
Andrzej Bieńkowski painter, ethnographer, author of documentary films, professor at the Academy of Fine Arts in Warsaw. Author of the books The Last Country Musicians (2001), The Sold Music (2007) and 1000 Kilometers of Music (2009). Since the 1980s, he and his wife Małgorzata have been conducting ethnographic research, recording and filming rural musicians and singing performances from Poland, Ukraine and Belarus. In 2012, they set up the Muzyka Odnaleziona foundation, which makes their huge archival collections available on CDs as well as on the website www.muzykaodnaleziona.pl and on a YouTube channel. They also implement the Rural Music Archive project (https://archiwummuzykiwiejskiej.pl/), which aims to collect, digitize and make available photographs documenting the musical culture of the countryside.